Beans (Phaseolus vulgaris) are an important part of the Costa Rican diet. - Rodríguez, Ligia (2004)
Nevertheless, the amount and the frequencyof its consumption has been decreasing over time, especiallyin the urban areas1 This tendency is a concern to thoseinvolved in health and nutrition since beans are a source ofprotein, non-heme iron, fiber, folic acid, thiamin, potassium,magnesium and zinc2. The nutritional contribution of beanslo the Costa Rican diet is important in spite of the reductionin consumption. Beans are important because of their nutrientcontent and the presence of phytochemicals that have beenrecognized as part of the prevention and treatment of healthproblems affecting the Costa Rican population3. This reviewdocuments the positive effects of some of the nutrients andelements present in beans related lo the prevention and controlof some chronic diseases of importance in public health.lt includes information on fiber, folic acid and magnesium.Additionally, it considers the presence of phytochemicais thatmake beans a “functional food”. Finally, some practicar recommendationsare offered in order lo improve digestibility.Thus, our purpose is to educate the Costa Rican population lomaintain and lo increase the consumption of beans.